Are we on the same page? The performance effects of congruence between supervisor and group trust. - Carter, Min Z.; Mossholder, Kevin W. (Journal of Applied Psychology, 2015)
Taking a multiple-stakeholder perspective, we examined the effects of supervisor-work group trust congruence on groups' task and contextual performance using a polynomial regression and response surface analytical framework. We expected motivation experienced by work groups to mediate the positive influence of trust congruence on performance. Although hypothesized congruence effects on performance were more strongly supported for affective rather than for cognitive trust, we found significant indirect effects on performance (via work group motivation) for both types of trust. We discuss the performance effects of trust congruence and incongruence between supervisors and work groups, as well as implications for practice and future research.